2019
DOI: 10.1038/s41598-018-36995-9
|View full text |Cite
|
Sign up to set email alerts
|

The protective value of a defensive display varies with the experience of wild predators

Abstract: Predation has driven the evolution of diverse adaptations for defence among prey, and one striking example is the deimatic display. While such displays can resemble, or indeed co-occur with, aposematic ‘warning’ signals, theory suggests deimatic displays may function independently of predator learning. The survival value of deimatic displays against wild predators has not been tested before. Here we used the mountain katydid Acripeza reticulata to test the efficacy of a putative deimatic display in the wild. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…Startle or deimatic displays involve behaviours wherein conspicuous colours are suddenly displayed, providing prey a survival advantage (Umbers, Lehtonen & Mappes, 2015; Umbers & Mappes, 2015). Although there has been disagreement regarding what constitutes a deimatic display and how it differs from aposematism (Ruxton, Sherratt & Speed, 2004; Umbers, Lehtonen & Mappes, 2015; Umbers & Mappes, 2015, 2016; Skelhorn, Holmes & Rowe, 2016), there is general agreement that deimatism involves a momentary transient display of conspicuous signal (Ruxton, Sherratt & Speed, 2004; Olofsson et al, 2012; Umbers & Mappes, 2016) that triggers an unlearnt avoidance response in predators (Umbers et al, 2017, 2019). While uropeltid colours could also have a deimatic function, our experiments show that birds avoided uropeltid snake models that were static (pinned to the ground) and did not show any momentary display of conspicuous colourations.…”
Section: Discussionmentioning
confidence: 99%
“…Startle or deimatic displays involve behaviours wherein conspicuous colours are suddenly displayed, providing prey a survival advantage (Umbers, Lehtonen & Mappes, 2015; Umbers & Mappes, 2015). Although there has been disagreement regarding what constitutes a deimatic display and how it differs from aposematism (Ruxton, Sherratt & Speed, 2004; Umbers, Lehtonen & Mappes, 2015; Umbers & Mappes, 2015, 2016; Skelhorn, Holmes & Rowe, 2016), there is general agreement that deimatism involves a momentary transient display of conspicuous signal (Ruxton, Sherratt & Speed, 2004; Olofsson et al, 2012; Umbers & Mappes, 2016) that triggers an unlearnt avoidance response in predators (Umbers et al, 2017, 2019). While uropeltid colours could also have a deimatic function, our experiments show that birds avoided uropeltid snake models that were static (pinned to the ground) and did not show any momentary display of conspicuous colourations.…”
Section: Discussionmentioning
confidence: 99%
“…We did not count this as consumption of the prey because birds did not taste the prey items and therefore did not receive any information about their palatability. Previous studies have also demonstrated that aposematic insects often survive an encounter with avian predators (Exnerová et al, ; Umbers et al, ; Wiklund & Järvi, ), and we assumed that picking up the prey without further handling would not ‘kill’ it. Nevertheless, handling by predators might have some fitness costs for prey.…”
Section: Methodsmentioning
confidence: 99%
“…Startle or deimatic displays involve behaviours wherein conspicuous colours are suddenly displayed, providing prey a survival advantage (Umbers, Lehtonen & Mappes, 2015;. Although there has been disagreement regarding what constitutes a deimatic display and how it differs from aposematism (Ruxton, Sherratt & Speed, 2004;Umbers, Lehtonen & Mappes, 2015;Skelhorn, Holmes & Rowe, 2016), there is general agreement that deimatism involves a momentary transient display of conspicuous signal (Ruxton, Sherratt & Speed, 2004;Olofsson et al, 2012;Umbers & Mappes, 2016) that triggers an unlearnt avoidance response in predators (Umbers et al, 2017(Umbers et al, , 2019. While uropeltid colours could also have a deimatic function, our experiments show that birds avoided uropeltid snake models that were static (pinned to the ground) and did not show any momentary display of conspicuous colourations.…”
Section: Discussionmentioning
confidence: 99%